Uji Kinerja Komposit TiO2-Graphene/Surfaktan dalam Mendegradasi Senyawa Fenol - Desi Heltina; Dwi Imamatul Mastura; Arif Partama (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2021)
Phenol is a hazardous compound that is often found in wastewater in most industries and cannot be degraded naturally. Photocatalysis is a promising method to reduce phenol waste, because it can produce more environmentally friendly compounds like CO2 and H2O. Titanium dioxide (TiO2) has been widely applied in the degradation process of waste compounds including phenol waste. To improve the performance of TiO2, graphene can be used as a dopants because it has a surface area. Modification of graphene with surfactants was carried out to increase dispersion and reduce agglomeration on TiO2 doped with graphene. The purpose of this research is to synthesize TiO2–graphene/surfactant composite which can be used to degrade phenolic compounds. Photodegradation of TiO2 composites was carried out by varying the initial concentration of phenol (10, 20, 30 ppm). Composites synthesis begins with disperse the surfactant on the surface of the graphene, then proceeds with doping graphene (surfactant) on TiO2. The resulting composites were characterized using SEM, BET, FTIR, XRD and UV-Vis spectrophotometer. The phenol degradation process was carried out using a photodegradation reactor. The highest performance TiO2–graphene/surfactant composite was obtained at an initial concentration of 10 ppm phenol is 81.02%